IMPLEMENTASI MODEL BELAJAR BERBASIS FORTOFOLIO DALAM MENINGKATKAN PEMAHAMAN MAHASISWA DALAM PENGEMBANGAN MEDIA PEMBELAJARAN - Reni Nurapriani; Agus Ruswandi; Riki Ruswandi (AWLADY : Jurnal Pendidikan Anak, 2020)
For managing learning and teaching there needs to be a suitable strategy to be able to organize learning so that it becomes better. One of the strategies that must be used by kindergarten teachers is the strategy in developing learning media. Learning media should be educational, economical, practical and contextual. To support this problem, the lecture who teach “Strategi Pembelajaran PAUD”, with based on fortfolio learning model. The method used in this research is quasy experiment with one group pre test posttest design model with independent t test. The results of this study indicate that the learning based on portfolio model can improve student understanding in terms of development strategies for kindergarten learning media with an average pretest of 54.00 and posttest increasing to 84.33. Based on the t test through SPSS it was concluded that there was a significant influence on the use of fortfolio-based learning on student understanding in developing learning media